Odpowiedzi

2010-04-13T16:02:51+02:00
-1/4 * (2 + x) = 3/4x
-1/4 * 2 - 1/4 * x = 3/4x
-0,5 - 1/4x = 3/4x
-0,5 = 3/4x + 1/4x
-0,5 = 4/4x
x = (-0,5)

-2 * (x + 1/2) - 3 * (x + 1/3) = 0
-2x - 1 - 3x - 1 = 0
-5x - 2 = 0
-5x = 0 + 2
-5x = 2
x = 2 : (-5)
x = (-0,4)

(x + 2) ∧ 6 = 0,5x
6x + 12 = 0,5x
12 = 0,5x - 16x
12 = (-15,5x)
x = 12 : (-15,5)
x = (-24/31)

0,1 * (x + 2) = 0,2x
0,1x + 0,2 = 0,2x
0,2 = 0,2x - 0,1x
0,2 = 0,1x
x = 0,2 : 0,1
x = 2

6 * (1 - 1/3x) = 2 * (1 + 1/2x)
6 - 2x = 2 + x
-2x - x = 2 - 6
-3x = (-4)
x = (-4) : (-3)
x = 1 1/3
2010-04-13T16:25:13+02:00
⁻¼(2+x)=³₄x
-½-¼x=¾x
-¼x-¾x=½
2x=½
x=¼

-2(x+½) - 3(x+⅓)=0
-2x-1-3x-1,5=0
-2x-3x=1+1,5
-5x=2,5 / *(-1)
5x=-2,5
x=-0,5

0,1(x+2)= 0,2x
0,1x+0,2=0,2x
0,1x-0,2x=0,2
-0,1x=0,2 /*(-1)
0,1x=-0,2
x=-2

6(1-⅓x)=2(1+½x)
6-3x=2+x
-3x-x=2-6
-4x=-4
x=1